Pristine Poly(para-phenylene): relating semiconducting behavior to kinetics of precursor conversion - Strunk, Karl-Philipp; Abdulkarim, Ali; Freudenberg, Jan; Pucci, Annemarie; Bunz, Uwe H. F.; Melzer, Christian; Müllen, Klaus (ACS applied materials & interfaces, 2019)
We investigated unsubstituted poly(para-phenylene) (PPP), a long-desired prototype of a conjugated polymer semiconductor. PPP was accessed via thermal aromatization of a precursor polymer bearing kinked, solubility-inducing dimethoxycyclohexadienylene moieties. IR spectroscopy and Vis ellipsometry studies revealed that the rate of conversion of the precursor to PPP increases with temperature and decreases with film density, indicating a process with high activation volume. The obtained PPP films were analyzed in thin-film transistors to gain insights into the interplay between the degree of conversion and the resulting p-type semiconducting properties. The semiconducting behavior of PPP was further unambiguously proven through IR and transistor measurements of molybdenum trioxide p-doped films.